2008
DOI: 10.1063/1.2898211
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a refractometric sensor based on optical microfiber coil resonator

Abstract: We experimentally demonstrated a refractometric sensor based on a coated optical microfiber coil resonator. It is robust, compact, and comprises an intrinsic fluidic channel. A sensitivity of about 40 nm/RIU ͑refractive index unit͒ has been measured, in agreement with predictions. © 2008 American Institute of Physics. ͓DOI: 10.1063/1.2898211͔ Evanescent-field-based optical resonators in the form of microspheres, photonic crystals, microdisks, microtoroids, and microrings have been under intensive investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 30 publications
0
87
0
1
Order By: Relevance
“…Examples include microfiber loop resonators [3], microsphere resonators [4], and microfiber coil resonators [5]. However they have either relatively low sensitivity, typically 40-800 nm/RIU, or they need complex manipulation of the microfibers to form the sensing structure.…”
mentioning
confidence: 99%
“…Examples include microfiber loop resonators [3], microsphere resonators [4], and microfiber coil resonators [5]. However they have either relatively low sensitivity, typically 40-800 nm/RIU, or they need complex manipulation of the microfibers to form the sensing structure.…”
mentioning
confidence: 99%
“…Though LPGs have been revealed to possess a high sensitivity to the refractive index of the ambient medium, the typical full width at half maximum of the resonance peak of a LPG is about tens of nanometers, which limits the measurement accuracy and its multiplexing capability. Most recently, optical refractive index sensors or refractometers based on all-fiber interferometers 16,17 or resonators 18 have received considerable attention for their high sensitivity, absolute detection with wavelength codified information, broad measurement range, and compact size. These fiber interferometric techniques are cumbersome systems with high cost and simultaneous sensing of refractive index and temperature is missing.…”
mentioning
confidence: 99%
“…Around the same time, Xu et al reported a loop resonator refractometric sensor embedded in polymer and studied the dependency of sensitivity on the MNF diameter and coating thickness [86]. Later, the same group demonstrated a refractometric sensor based on optical microfiber coil resonator and achieved a sensitivity of about 40 nm/ RIU by using a 2.5-μm-diameter MNF wrapping around a 1-mm-diameter rod with a total sensing length of about 50 mm [159]. In 2009, Scheuer proposed an optical rotation sensor based on a fiber microcoil resonator.…”
Section: Mnf Sensorsmentioning
confidence: 98%